POT-3 preferentially binds the terminal DNA-repeat on the telomeric G-overhang. Issue 2 (30th December 2022) - Yu, Xupeng; Gray, Sean; Ferreira, Helder C
Abstract: Eukaryotic chromosomes typically end in 3′ telomeric overhangs. The safeguarding of telomeric single-stranded DNA overhangs is carried out by factors related to the protection of telomeres 1 (POT1) protein in humans. Of the three POT1-like proteins in Caenorhabditis elegans, POT-3 was the only member thought to not play a role at telomeres. Here, we provide evidence that POT-3 is a bona fide telomere-binding protein. Using a new loss-of-function mutant, we show that the absence of POT-3 causes telomere lengthening and increased levels of telomeric C-circles. We find that POT-3 directly binds the telomeric G-strand in vitro and map its minimal DNA binding site to the six-nucleotide motif, GCTTAG. We further show that the closely related POT-2 protein binds the same motif, but that POT-3 shows higher sequence selectivity. Crucially, in contrast to POT-2, POT-3 prefers binding sites immediately adjacent to the 3′ end of DNA. These differences are significant as genetic analyses reveal that pot-2 and pot-3 do not function redundantly with each other in vivo . Our work highlights the rapid evolution and specialisation of telomere binding proteins and places POT-3 in a unique position to influence activities that control telomere length.